Case Report: Hepatic Artery Infusion Chemotherapy After Stage I ALPPS in a Patient With Huge HCC - Zhuo, Wenfeng; Li, Ang; Yang, Weibang; Duan, Jinxin; Min, Jun; Wei, Jinxing (Frontiers in Surgery, 2021)
Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) can induce rapid hypertrophy of the liver remnant. But with a background of liver cirrhosis or other chronic liver diseases, patients with a huge hepatocellular carcinoma (HCC) may sometimes face insufficiency of hepatocellular regeneration after ALPPS. Herein, we report a 56-year-old male with a vast HCC (13.3 × 8.5 × 13.0cm) whose ratio of the future liver remnant (FLR)/standard liver volume (SLV) was 28.7% when first diagnosed. Inadequate hypertrophy of FLR was shown in postoperative volumetric assessment a month after stage I ALPPS. After multidisciplinary team discussion (MDT), the patient was decided to follow three courses of hepatic arterial infusion chemotherapy (HAIC) with oxaliplatin, fluorouracil, and leucovorin (FOLFOX4), with the last HAIC combining with transhepatic arterial embolization (TAE), and the ratio of FLR/SLV finally increased from 28.7% to 40% during three-month intervals, meeting the requirements of the surgery. Stage II ALPPS— right trisectionectomy, was then successfully performed. There was no recurrence at half years of follow-up. In our case, HAIC seems to be more potent than transcatheter arterial chemoembolization (TACE) in maintaining the hyperplasia of the liver remnant, reducing tumor load, and preventing tumor progression for patients with a large HCC during ALPPS procedure. HAIC following the first step of ALPPS— a pioneering treatment modality aiming for inadequate hypertrophy of FLR induced by ALPPS, could be an alternative procedure for patients with a vast HCC in clinical practice.